The Influence of the Work Environment and Interpersonal Communication on Job Satisfaction: Study on Office Employees of Tambahrejo Subdistrict - Purwati, Purwati; Trisnawati, Novi (Journal of Office Administration : Education and Practice, 2023)
This research aims to determine 1) The influence of the work environment on job satisfaction at the Tambahrejo subdistrict office, 2) The influence of interpersonal communication on job satisfaction at the Tambahrejo subdistrict office, 3) The influence of the work environment and interpersonal communication on job satisfaction at the Tambahrejo subdistrict office. This research uses a quantitative approach with a correlation or correlational (relationship) type of research. The population and sample for this study were 26 employees of the Tambahrejo subdistrict office. The data collection method is through a questionnaire with the data analysis technique used, namely multiple linear regression analysis. The results obtained in this research are that there is an insignificant influence between the work environment and job satisfaction, interpersonal communication has a significant effect on job satisfaction, and the work environment and interpersonal communication simultaneously influence job satisfaction with the value of the work environment and interpersonal communication on job satisfaction which is tested by the coefficient determination (R2) obtained an R Square coefficient of determination of 0.470, which means that all independent variables together contribute 47.0% to job satisfaction, while the remaining 53.0% is caused by other factors not tested in this research.